Mesenchymal Stem Cells and their Derived Exosomes Promote Malignant Phenotype of Polyploid Non-Small-Cell Lung Cancer Cells through AMPK Signaling Pathway. (4th April 2022) - Wang, Lili; Ouyang, Mingyue; Xing, Sining; Zhao, Song; Liu, Shuo; Sun, Lingyan; Yu, Huiying
Abstract : Chemotherapy is an important method for the treatment of non-small-cell lung cancer (NSCLC), but it can lead to side effects and polyploid cancer cells. The polyploid cancer cells can live and generate daughter cancer cells via budding. Mesenchymal stem cells (MSCs) are pluripotent stem cells with repair and regeneration functions and can resist tissue damage caused by tumor therapy. This study is aimed at investigating the effects of MSCs and their derived exosomes on the biological characteristics of polyploid NSCLC cells and the potential mechanisms. We found that MSC conditioned medium (CM), MSCs, and MSC-exosomes had no effect on cell proliferation of the polyploid A549 and H1299 cells. Compared with the control group, MSCs and MSC-exosomes significantly promoted epithelial mesenchymal transformation, cell migration, antiapoptosis, and autophagy in the polyploid A549 and H1299 by activating AMPK signaling pathway, but no significant changes were observed in MSC-CM treatment. These results revealed that MSCs and MSC-exosomes promoted malignant phenotype of polyploid NSCLC cells through the AMPK signaling pathway.